Polymerization of Biobased Farnesene in Miniemulsions by Nitroxide-Mediated Polymerization - Luk, Sharmaine B. (ACS Omega, 2021)
[Image: see text] Biobased farnesene (Far) was polymerized by nitroxide-mediated polymerization in miniemulsions using two different alkoxyamine initiators, the SG1-based and succinimidyl-modified BlocBuilder (NHS-BB) and Dispolreg 007 (D7). Stable emulsions were observed after 30 h of reaction at 90 °C, where NHS-BB-initiated systems resulted in smaller particles (∼300 nm) than using D7 (∼400 nm). Successful chain extension of the poly(Far) macroinitiators (24,500–39,700 g mol(–1)) with styrene were achieved using 15 wt % surfactant relative to monomer concentration. Compartmentalization effects were not observed in these emulsions as the polymerization rate was still much slower compared to the bulk, even though Z-averaged particle sizes were around 300–400 nm. Finally, all biobased diblock copolymers were synthesized by chain-extending poly(Far) macroinitiators with isobornyl methacrylate (iBOMA), where the D7 initiator showed more effective chain extension (less unreacted macroinitiator) than NHS-BB.